Theory, evidence and Intervention Mapping to improve behavior nutrition and physical activity interventions - Ferreira Isabel; Oenema Anke; Brug Johannes (BMC, 2005)
Abstract Background The present paper intends to contribute to the debate on the usefulness and barriers in applying theories in diet and physical activity behavior-change interventions. Discussion Since behavior theory is a reflection of the compiled evidence of behavior research, theory is the only foothold we have for the development of behavioral nutrition and physical activity interventions. Application of theory should improve the effectiveness of interventions. However, some of the theories we use lack a strong empirical foundation, and the available theories are not always used in the most effective way. Furthermore, many of the commonly-used theories provide at best information on what needs to be changed to promote healthy behavior, but not on how changes can be induced. Finally, many theories explain behavioral intentions or motivation rather well, but are less well-suited to explaining or predicting actual behavior or behavior change. For more effective interventions, behavior change theory needs to be further developed in stronger research designs and such change-theory should especially focus on how to promote action rather than mere motivation. Since voluntary behavior change requires motivation, ability as well as the opportunity to change, further development of behavior change theory should incorporate environmental change strategies. Conclusion Intervention Mapping may help to further improve the application of theories in nutrition and physical activity behavior change.